Plan de incentivos laborales en la cooperativa de ahorro y crédito Virgen del Cisne - Aguilar Tandalla, Alexander Matías (2023)
In the present research work, the objective is to design a work incentives plan in the "Virgen del Cisne" savings and credit cooperative, part of the problem of low work performance of 26.69% of employees, presented in the first semester. of the year 2022, since the incentives are linked to the productivity of the organizations. It is a study with a quantitative approach, to analyze data collected from employees with the instrument of questions about work incentives. In the cooperative, with the intention of understanding in a clear and concise way, we analyze the job profiles of the employees of the financial institution, as well as the job performance of the employees.